Lithium battery polyimide binder and preparation method thereof

By using isocyanate-capped fat chain oligomers, rigid structural oligomers and carboxyl-containing functional substances synthesized, the problem of insufficient slurry stability in the production of electrode sheets in the prior art is solved, and high-performance electrode sheet production and battery performance improvement are achieved.

CN119529749APending Publication Date: 2025-02-28CHANGZHOU HUANFENG ELECTRICAL MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411713716.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium-electric polyimide binder has the problem of insufficient slurry stability in the production of electrode sheets, which affects the service life and performance of the battery.

Method used

High-performance lithium-electric polyimide binders are synthesized by specific preparation methods using isocyanate-capped fat chain oligomers, rigid structural oligomers and carboxyl-containing functional substances.

Benefits of technology

The storage stability and peeling force of the positive electrode slurry are improved, the production stability of the electrode sheet is extended, the aggregation and precipitation of the slurry are avoided, and the performance of the lithium-ion battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156395940000021
    Figure BDA0005156395940000021
  • Figure BDA0005156395940000022
    Figure BDA0005156395940000022
  • Figure BDA0005156395940000031
    Figure BDA0005156395940000031
Patent Text Reader

Abstract

The invention belongs to the field of binders (IPC classification number: C09J), and particularly relates to a lithium battery polyimide binder and a preparation method thereof. The first aspect of the invention provides the polyimide binder for the lithium battery. The polyimide binder comprises the following raw materials: an isocyanate-terminated aliphatic chain-containing oligomer, a rigid structure oligomer and a functional substance; the cyanate-terminated aliphatic chain-containing oligomer comprises a hydroxyl group and / or an amino group. When the obtained polyimide binder for the lithium battery is used in positive electrode slurry, the positive electrode slurry does not agglomerate and precipitate after standing, and the positive electrode slurry without using the binder can agglomerate after being kept for at most 20 hours, so that the positive effect of the binder on the stability of the positive electrode slurry is further indicated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of adhesives, and specifically relates to a lithium battery polyimide adhesive and a preparation method thereof. Background Art

[0002] Lithium battery polyimide binder is a high temperature, high strength, high stability binder made of polyimide (PI) material. Polyimide binder is widely used in positive and negative electrode materials of lithium-ion batteries. Lithium battery polyimide binder can fully combine with positive and negative electrode materials to form a stable structure, prevent the electrodes from loosening or falling off, thereby improving the service life and performance of the battery.

[0003] Chinese invention patent CN105609780B discloses an electrode binder, a positive electrode material and a lithium-ion battery. In the disclosed patent, it is disclosed that a polyimide polymer is obtained by polymerization of a diamine monomer and a dianhydride monomer, and the molecular weight of the binder obtained by polymerization of the dianhydride monomer and the diamine monomer is 1000 to 50000. The polymer obtained by polymerization of the diamine monomer and the dianhydride monomer can be used as a positive electrode binder in lithium-ion batteries, and has little effect on the charge and discharge cycle performance of the lithium-ion battery, and can improve the electrode stability and thermal stability of the lithium-ion battery. However, the disclosed patent does not disclose that the polymer has a specific positive effect on the thermal stability of the positive or negative electrode materials, and the performance of the polymer itself has not been verified.

[0004] With the continuous development of lithium-ion battery technology, the performance requirements for binders are getting higher and higher. As a high-performance binder material, lithium battery polyimide binder has broad development prospects. How to prepare a binder with good performance, especially in terms of slurry stability, can play a positive role and have a great impact on the production of pole pieces. Therefore, in the current situation of rapid development of lithium batteries, how to improve the performance of binders and ensure the quality of pole piece production is an important part of the development of lithium batteries. Summary of the invention

[0005] In order to further improve the quality of pole piece production, the first aspect of the present invention provides a lithium battery polyimide binder, the raw materials include isocyanate-terminated fatty chain oligomers, rigid structure oligomers, and functional substances;

[0006] The cyanate-terminated fatty chain-containing oligomer includes hydroxyl and / or amino groups;

[0007] The functional substances include chemical substances containing carboxyl groups.

[0008] As a preferred embodiment, the isocyanate-terminated fatty chain-containing oligomer includes at least one of an isocyanate-terminated difunctional hydroxyl oligomer, an isocyanate-terminated trifunctional hydroxyl oligomer, and an isocyanate-terminated tetrafunctional hydroxyl oligomer.

[0009] Further preferably, the isocyanate-terminated fatty chain-containing oligomer comprises an isocyanate-terminated difunctional hydroxyl oligomer.

[0010] Further preferably, the raw material of the isocyanate-terminated difunctional hydroxyl oligomer includes a diol; more preferably, the diol includes a polyester diol and / or an aliphatic diol.

[0011] As a preferred embodiment, the molecular structure of the aliphatic diol is represented by formula (1), specifically:

[0012]

[0013] n is a positive integer from 2 to 10.

[0014] As a preferred embodiment, the structural formula of the polyester diol is represented by formula (2), specifically:

[0015]

[0016] R represents a methyl group or an ethyl group.

[0017] As a preferred embodiment, the polyester diol includes poly(1,4-butylene adipate) diol; specific examples include: PBA-1000, PBA-2000, PBA-3000, PBA-4000, and PBA-5000.

[0018] As a preferred embodiment, the polyester diol includes sebacic acid polyester polyol; specifically, THCM-2800 can be cited.

[0019] As a preferred embodiment, the isocyanate-terminated fatty chain-containing oligomer includes an isocyanate-terminated difunctional amino oligomer, an isocyanate-terminated trifunctional amino oligomer, and an isocyanate-terminated tetrafunctional amino oligomer.

[0020] Further preferably, the isocyanate-terminated fatty chain-containing oligomer comprises an isocyanate-terminated difunctional amino oligomer.

[0021] As a preferred embodiment, the raw materials of the isocyanate-terminated difunctional amino oligomer include aliphatic diamine.

[0022] More preferably, the structural formula of the aliphatic diamine is represented by formula (3), specifically:

[0023]

[0024] n is a positive integer from 4 to 10.

[0025] As a preferred embodiment, the number average molecular weight of the isocyanate-terminated fatty chain oligomer is 100-50,000; preferably, the number average molecular weight of the isocyanate-terminated fatty chain oligomer is 100-30,000; more preferably, the number average molecular weight of the isocyanate-terminated fatty chain oligomer is 500-20,000.

[0026] As a preferred embodiment, the raw materials of the rigid structure oligomer include monomers containing aromatic structures and isocyanate.

[0027] As a preferred embodiment, the rigid structure in the rigid structure oligomer includes at least one of diaminodiphenylmethane, diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, diaminodiphenyl sulfone, 3,3-dichloro-4,4-diaminophenylmethane, 4,4-diamino-2,2-bistrifluoromethylbiphenyl, trimellitic anhydride, and terephthalic anhydride.

[0028] More preferably, the raw material of the rigid structure oligomer includes one of diaminodiphenyl ether and diaminodiphenylmethane.

[0029] More preferably, the raw material of the rigid structure oligomer includes diaminodiphenyl ether.

[0030] As a preferred embodiment, the number average molecular weight of the rigid structure oligomer is 100-50000; preferably, the number average molecular weight of the rigid structure oligomer is 100-30000; more preferably, the number average molecular weight of the rigid structure oligomer is 500-20000.

[0031] As a preferred embodiment, the functional substance includes a chemical substance containing a carboxyl group.

[0032] As a preferred embodiment, the carboxyl-containing chemical substance includes at least one of diaminobenzoic acid, dimethylolbutyric acid, dimethylolpropionic acid, polyacrylic acid, polybutenoic acid, and polyaspartic acid-polyethylene glycol-carboxyl.

[0033] As a preferred embodiment, the amount of the functional substance added is 1-20% of the total weight of the raw materials in the system; preferably, the amount of the functional substance added is 1-15% of the total weight of the raw materials in the system.

[0034] More preferably, the amount of the functional substance added is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% of the total weight of the raw materials in the system.

[0035] During the experiment, the applicant found that the amount of functional substance added had a great influence on the performance of the final prepared binder. When the amount of functional substance added was less than 1% of the total weight of the raw materials in the system, the storage stability of the positive electrode slurry would not be improved; when the amount of functional substance added was higher than 20% of the total weight of the raw materials in the system, the thixotropic time of the positive electrode slurry would be too fast, affecting the normal production of the pole piece, and the pole piece peeling force would not continue to increase after reaching 100N / m.

[0036] As a preferred embodiment, the isocyanate used in the process of preparing the adhesive includes a diisocyanate, and the diisocyanate is selected from at least one of MDI (diphenylmethane diisocyanate), TDI (toluene diisocyanate), HDI (hexamethylene diisocyanate), HMDI (dicyclohexylmethane diisocyanate), NDI (1,5-naphthalene diisocyanate), and IPDI (isophorone diisocyanate).

[0037] As a preferred embodiment, the raw materials for preparing the adhesive further include a solvent.

[0038] Further preferably, the solvent can be used as long as it can dissolve the raw materials in the present application and provide conditions for chemical reactions.

[0039] More preferably, the solvent includes one of NMP (N-methyl-2-pyrrolidone), DMF (dimethylformamide), and DMAC (dimethylacetamide).

[0040] In some preferred embodiments, the raw materials for preparing the lithium battery polyimide binder include 15-25 parts of diol and / or aliphatic diamine, 50-150 parts of isocyanate, 20-60 parts of monomer containing aromatic structure, 500-600 parts of solvent, and 3-10 parts of functional substance.

[0041] The second aspect of the present invention provides a method for preparing a lithium battery polyimide binder, comprising the following steps:

[0042] S1 Preparation of isocyanate terminated fatty chain oligomers;

[0043] S2 Preparation of rigid structure oligomers;

[0044] Preparation of polyimide binder for S3 lithium battery.

[0045] As a preferred implementation, the step S3 specifically includes:

[0046] Add the functional substances into the mixture and stir well.

[0047] The reaction formula of the preparation method of the lithium battery polyimide binder is shown in formula (4):

[0048]

[0049] R1, R2, and R3 in formula (4) can all represent a benzene ring, an aliphatic six-membered ring, a methyl group, or an ethyl group.

[0050] As a preferred embodiment, the method for preparing the isocyanate-terminated fatty chain-containing oligomer comprises the following steps:

[0051] Dissolve isocyanate in a solvent, gradually add diol or aliphatic diamine, and react at 40-80° C. for 1-5 hours to obtain an isocyanate-terminated fatty chain-containing oligomer with a solid content of 30-70 wt%.

[0052] As a preferred embodiment, the method for preparing the rigid structure oligomer comprises the following steps:

[0053] The raw materials of the rigid structure oligomer are dissolved in a solution, heated to 45-60° C., and then isocyanate is added and reacted at 40-80° C. for 1-5 hours to obtain a rigid structure oligomer with a solid content of 30-70wt%.

[0054] As a preferred embodiment, the preparation method of the lithium battery polyimide binder comprises the following steps:

[0055] Take an isocyanate-terminated fatty chain oligomer and a rigid structure oligomer, mix them evenly, react them at 60-90° C. for 1-5 hours, then add a functional substance, stir evenly, and obtain a polyimide adhesive.

[0056] Another aspect of the present invention also provides an application of a lithium battery polyimide binder for use in positive electrode slurry.

[0057] The raw materials for preparing the positive electrode slurry include, by weight, 5-15 parts of a polyimide binder, 50-100 parts of lithium iron phosphate, 0.05-0.5 parts of conductive carbon black, 10-50 parts of N-methyl-2-pyrrolidone, and 50-150 parts of zirconium beads.

[0058] The preparation method of the positive electrode slurry comprises the following steps: uniformly dispersing all the preparation raw materials using a homogenizer, filtering out the zirconium beads using a filter screen, and then coating on aluminum foil with a coating thickness of 100-300 μm.

[0059] The above technical solution has the following advantages or beneficial effects:

[0060] 1. The lithium battery polyimide binder prepared by the present invention can improve the storage stability of the positive electrode slurry when used in the positive electrode slurry.

[0061] 2. When the lithium battery polyimide binder prepared by the present invention is used in the positive electrode slurry, the peeling force of the positive electrode sheet can be increased to 100N / m.

[0062] 3. When the lithium battery polyimide binder obtained by the present invention is used in the positive electrode slurry, the positive electrode slurry will not agglomerate or precipitate after standing, while the positive electrode slurry without this binder will agglomerate after being kept for a maximum of 20 hours, which further illustrates the positive role of the binder in the stability of the positive electrode slurry. DETAILED DESCRIPTION

[0063] The following will be combined with specific cases in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] In the present application, the substance obtained in the preparation of the isocyanate-terminated fatty chain oligomer in step S1 is recorded as M1; the substance obtained in the preparation of the rigid structure oligomer in step S2 is recorded as M2.

[0065] Example

[0066] Example 1

[0067] S1 Preparation of isocyanate-terminated fatty chain oligomers:

[0068] 50.1 g of MD1 was dissolved in 70.3 g of NMP solution, and 20.2 g of 1,12-dodecanediol was gradually added, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated fatty chain oligomer M1 with a solid content of 50 wt%.

[0069] Preparation of S2 rigid structure oligomers:

[0070] 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP solution, heated to 50° C., and 25 g of MDI was gradually added, and reacted at 50° C. for 2 h to obtain a rigid structure oligomer M2 with a solid content of 50 wt%.

[0071] Preparation of S3 lithium battery polyimide binder:

[0072] Take 140.6 g of M1 and 130 g of M2, mix them evenly, react at 80° C. for 3 h, and gradually add 406 g of NMP to obtain a polymer solution with a mass concentration of 20%.

[0073] 5.4 g of polyacrylic acid and 21.6 g of NMP were added to the above polymer solution and stirred thoroughly.

[0074] Example 2

[0075] S1 Preparation of isocyanate-terminated fatty chain oligomers:

[0076] 50.1 g of MD1 was dissolved in 70.3 g of NMP solution, and 20.2 g of 1,12-dodecanediol was gradually added, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated fatty chain oligomer M1 with a solid content of 50 wt%.

[0077] Preparation of S2 rigid structure oligomers:

[0078] 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP solution, heated to 50° C., and 25 g of MDI was gradually added, and reacted at 50° C. for 2 h to obtain a rigid structure oligomer M2 with a solid content of 50 wt%.

[0079] 3) Preparation of lithium battery polyimide binder:

[0080] Take 140.6g of M1 and 130g of M2, mix them evenly, react at 80°C for 3h, and gradually add 406g of NMP to obtain a polymer solution with a mass concentration of 20%. Add 13.5g of polyacrylic acid and 54g of NMP to the above polymer solution and stir well.

[0081] Example 3

[0082] S1 Preparation of isocyanate-terminated fatty chain oligomers:

[0083] 50.1 g of MD1 was dissolved in 70.3 g of NMP solution, and 20.2 g of 1,12-dodecanediol was gradually added, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated fatty chain oligomer M1 with a solid content of 50 wt%.

[0084] Preparation of S2 rigid structure oligomers:

[0085] 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP solution, heated to 50° C., and 25 g of MDI was gradually added, and reacted at 50° C. for 2 h to obtain a rigid structure oligomer M2 with a solid content of 50 wt%.

[0086] 3) Preparation of lithium battery polyimide binder:

[0087] Take 140.6g of M1 and 130g of M2, mix them evenly, react at 80°C for 3h, and gradually add 406g of NMP to obtain a polymer solution with a mass concentration of 20%. Add 27.1g of polyacrylic acid and 108g of NMP to the above polymer solution and stir well.

[0088] Example 4

[0089] S1 Preparation of isocyanate-terminated fatty chain oligomers:

[0090] 50.1 g of MD1 was dissolved in 70.3 g of NMP solution, and 20.2 g of 1,12-dodecanediol was gradually added, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated fatty chain oligomer M1 with a solid content of 50 wt%.

[0091] Preparation of S2 rigid structure oligomers:

[0092] 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP solution, heated to 50° C., and 25 g of MDI was gradually added, and reacted at 50° C. for 2 h to obtain a rigid structure oligomer M2 with a solid content of 50 wt%.

[0093] 3) Preparation of lithium battery polyimide binder:

[0094] Take 140.6g of M1 and 130g of M2, mix them evenly, react at 80°C for 3h, and gradually add 406g of NMP to obtain a polymer solution with a mass concentration of 20%. Add 13.5g of polybutenoic acid and 54g of NMP to the above polymer solution and stir well.

[0095] Example 5

[0096] S1 Preparation of isocyanate-terminated fatty chain oligomers:

[0097] 50.1 g of MD1 was dissolved in 70.3 g of NMP solution, and 20.2 g of 1,12-dodecanediol was gradually added, and the mixture was reacted at 60° C. for 2 h to obtain an isocyanate-terminated fatty chain oligomer M1 with a solid content of 50 wt%.

[0098] Preparation of S2 rigid structure oligomers:

[0099] 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP solution, heated to 50° C., and 25 g of MDI was gradually added, and reacted at 50° C. for 2 h to obtain a rigid structure oligomer M2 with a solid content of 50 wt%.

[0100] 3) Preparation of lithium battery polyimide binder:

[0101] Take 140.6g of M1 and 130g of M2, mix them evenly, react at 80℃ for 3h, and gradually add 406g of NMP to obtain a polymer solution with a mass concentration of 20%. Add 13.5g of aspartic acid-polyethylene glycol-carboxyl and 54g of NMP to the above polymer solution and stir well.

[0102] Comparative Example 1

[0103] Akema PVDF HSV900 is used to replace the binder in Example 1 of the present invention.

[0104] Comparative Example 2

[0105] S1 Preparation of isocyanate-terminated fatty chain oligomers:

[0106] 50.1 g of MDI was dissolved in 70.3 g of NMP solution, and 20.2 g of 1,12-dodecanediol was gradually added, and the reaction was carried out at 60° C. for 2 h to obtain an isocyanate-terminated fatty chain oligomer M1 with a solid content of 50 wt%.

[0107] Preparation of S2 rigid structure oligomers:

[0108] 40 g of diaminodiphenyl ether was dissolved in 65 g of NMP solution, heated to 50° C., and 25 g of MD1 was gradually added. The reaction was carried out at 50° C. for 2 h to obtain a rigid structure oligomer M2 with a solid content of 50 wt%.

[0109] 3) Preparation of lithium battery polyimide binder:

[0110] Take 140.6 g of M1 and 130 g of M2, mix them evenly, react at 80° C. for 3 h, and gradually add 406 g of NMP solvent to obtain a polymer solution with a mass concentration of 20%.

[0111] Performance Testing:

[0112] The binders of Examples 1-5 and Comparative Example 2 were used to prepare positive electrode slurry. The raw materials for preparing the positive electrode slurry are shown in Table 1 below:

[0113] Table 1:

[0114]

[0115] The raw materials of the positive electrode slurry prepared in Comparative Example 1 are shown in Table 2 below:

[0116] Table 2:

[0117]

[0118] 1. Peel force test:

[0119] The positive electrode sheets of Examples 1-5 and Comparative Examples 1-2 were subjected to a peeling force test:

[0120] The raw materials of the positive electrode slurry were dispersed evenly using a homogenizer, and the zirconium beads were filtered out using a 50 μm pore size filter. The coating thickness was controlled at 200 μm, and the mixture was dried at 130° C. and tested after drying.

[0121] The test was conducted with reference to GB / T2790-1995; the substrate was aluminum foil, and the width of the aluminum foil was 2.5 cm.

[0122] 2. Thixotropy test:

[0123] The dispersed positive electrode slurry was measured at 25°C using a BROOKFIELD rotary viscometer 63# rotor at different speeds of 1 to 60 rpm, and the slurry viscosity was 3000±500cp. Then it was placed in a vacuum environment at 25°C, and the viscosity at different speeds (1 to 60 rpm) was measured every 1h. If the slurry viscosity showed a significant change with the measured speed (viscosity fluctuated between 3000 and 10000cp, the speed gradually increased, and the viscosity gradually decreased), it means that the slurry has a thixotropic phenomenon.

[0124] 3. Cathode slurry stability test:

[0125] Place the dispersed positive electrode slurry in a vacuum environment at 25°C. Take 0.5g of the upper and lower slurries after each placement every 2 hours, and measure the mass concentration of the upper and lower slurries (dry at 180°C for 3 hours). If the mass concentration of the lower slurry minus the mass concentration of the upper slurry > 1%, it indicates that agglomeration has occurred. The test duration is 24 hours;

[0126] The test results are shown in Table 3 below:

[0127] Table 3:

[0128] Example Peel force N / m Time / h Time / h Example 1 40 10 No reunion Example 2 100 5 No reunion Example 3 50 2 No reunion Example 4 90 5 No reunion Example 5 75 3 No reunion Comparative Example 1 25 No thixotropy 20 Comparative Example 2 15 No thixotropy 14

[0129] It can be seen from the above performance test results that when the lithium battery polyimide binder obtained by the present invention is used in the positive electrode slurry, the positive electrode slurry will not agglomerate or precipitate after standing, while the positive electrode slurry without this binder will agglomerate after being kept for a maximum of 20 hours, and the positive electrode slurry with the binder of the present application will not agglomerate for more than 24 hours, which further illustrates the positive role of the binder in the stability of the positive electrode slurry.

Claims

1. A lithium battery polyimide binder, characterized in that: The raw materials include isocyanate-terminated oligomers containing fatty chains, rigid structure oligomers, and functional substances; The cyanate-terminated fatty chain-containing oligomer includes hydroxyl and / or amino groups; The functional substances include chemical substances containing carboxyl groups.

2. The lithium battery polyimide binder according to claim 1, characterized in that: The isocyanate-terminated fatty chain-containing oligomer includes at least one of an isocyanate-terminated difunctional hydroxyl oligomer, an isocyanate-terminated trifunctional hydroxyl oligomer, and an isocyanate-terminated tetrafunctional hydroxyl oligomer.

3. The lithium battery polyimide binder according to claim 1 or 2, characterized in that: The isocyanate-terminated fatty chain-containing oligomers include isocyanate-terminated difunctional amino oligomers, isocyanate-terminated trifunctional amino oligomers, and isocyanate-terminated tetrafunctional amino oligomers.

4. The lithium battery polyimide binder according to claim 3, characterized in that: The number average molecular weight of the isocyanate-terminated fatty chain oligomer is 100-50,000; preferably, the number average molecular weight of the isocyanate-terminated fatty chain oligomer is 100-30,000; more preferably, the number average molecular weight of the isocyanate-terminated fatty chain oligomer is 500-20,000.

5. The lithium battery polyimide binder according to claim 1, characterized in that: The rigid structure in the rigid structure oligomer includes at least one of diaminodiphenylmethane, diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, diaminodiphenyl sulfone, 3,3-dichloro-4,4-diaminophenylmethane, 4,4-diamino-2,2-bistrifluoromethylbiphenyl, trimellitic anhydride, and terephthalic anhydride.

6. The lithium battery polyimide binder according to claim 1, characterized in that: The carboxyl-containing chemical substance includes at least one of diaminobenzoic acid, dimethylolbutyric acid, dimethylolpropionic acid, polyacrylic acid, polybutenoic acid, and polyaspartic acid-polyethylene glycol-carboxyl.

7. The lithium battery polyimide binder according to claim 6, characterized in that: The added amount of the functional substance is 1-20% of the total weight of the raw materials in the system.

8. The lithium battery polyimide binder according to claim 6 or 7, characterized in that: The added amount of the functional substance is 1-15% of the total weight of the raw materials in the system.

9. A method for preparing a lithium battery polyimide binder according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1 Preparation of isocyanate terminated fatty chain oligomers; S2 Preparation of rigid structure oligomers; Preparation of polyimide binder for S3 lithium battery.

10. The method for preparing the electric polyimide adhesive according to claim 9, characterized in that: The S3 step specifically includes: Add the functional substances into the mixture and stir well.

Citation Information

Patent Citations

  • Electrode binders, positive electrode materials, and lithium-ion batteries

    CN105609780B